Water-use strategies in two co-occurring Mediterranean evergreen oaks: surviving the summer drought - David, T. S.; Henriques, M. O.; Kurz-Besson, C.; Nunes, J.; Valente, F.; Vaz, M.; Pereira, J. S.; Siegwolf, R.; Chaves, M. M.; Gazarini, L. C.; David, J. S. (Tree Physiology, 2007)
In the Mediterranean evergreen oak woodlands of southern Portugal, the main tree species are Quercus ilex ssp. rotundifolia Lam. (holm oak) and Quercus suber L. (cork oak). We studied a savannah-type woodland where these species coexist, with the aim of better understanding the mechanisms of tree adaptation to seasonal drought. In both species, seasonal variations in transpiration and predawn leaf water potential showed a maximum in spring followed by a decline through the rainless summer and a recovery with autumn rainfall. Although the observed decrease in predawn leaf water potential in summer indicates soil water depletion, trees maintained transpiration rates above 0.7 mm day−1 during the summer drought. By that time, more than 70% of the transpired water was being taken from groundwater sources. The daily fluctuations in soil water content suggest that some root uptake of groundwater was mediated through the upper soil layers by hydraulic lift. During the dry season, Q. ilex maintained higher predawn leaf water potentials, canopy conductances and transpiration rates than Q. suber. The higher water status of Q. ilex was likely associated with their deeper root systems compared with Q. suber. Whole-tree hydraulic conductance and minimum midday leaf water potential were lower in Q. ilex, indicating that Q. ilex was more tolerant to drought than Q. suber. Overall, Q. ilex seemed to have more effective drought avoidance and drought tolerance mechanisms than Q. suber.
10.1093/treephys/27.6.79310.1093/treephys/27.6.793
Keywords: canopy conductance; groundwater; Hydraulic conductance; leaf water potential; Quercus ilex; Quercus suber; sap flow

The effect of individual tree shelters in growth and morphology of cork oak seedlings - Dias, A. S.; Tomé, J.; Tavares, P.; Nunes, J.; Pereira, J. S. (SCIENTIA gerundensis, 1992)
To study the effects of the tree shelters in growth and morphology of cork oak ( Quercus suber L.) seedlings two types of plastic shelters were used in this work: A, transparent PVC shelters (brown) reinforced withawhitepolyesternet, 75 cmofheight; B, translucentbrownpolypropilene, double w$led, square cross section and 120 cm of height. The plants were grown in 120 cm long tubes in Evora, Portugal and growth of sheltered and control plants was evaluated based upon measurements of height, branch lenght, number and area of leaves and biomass. Additionally the anatomy and morphology and heat tolerance of leaves of sheltered andcontrolplants was studied. The results sbow that prowth in beight was stimulated by shelters. The amount of branches was greater in seedlings with shelters seedlings in shelters B were not significant. The shootíroot ratio was higher in sheltered plants than in controls because of the above-ground biomass increased in the former whereas root biomass remained unchanged. Foliage developed inside the shelters showed characteristics of acclimation to shade and were less tolerant to heat being killed at lower temperatures than those of unsheltered controls. A than in controls but the differences between the latter and
Keywords: Acclimation to shade; heat tolerance; Quercus suber; tree shelters